The Association between Sex, Knowledge, and Education Level of Evidence-Based Dentistry Behavior among Dentistry Student - Oki Fadhila1 , Aryo Dwipo Kusumo2 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Almost all faculties of dentistry have implemented Evidence Based Dentistry (EBD) curriculumto improve students ability to provide the best treatment for patients supported by the best research evidence,but there is still little data to show evaluations in their use. Objective: The aim of this study was to determinethe association between sex, knowledge, and education level of evidence-based dentistry behavior amongdentistry students. Method: The study was a cross sectional survey and has received ethical approval. Selfadministrated questionnaires distributed to second, third and fourth year students of the Faculty of DentalMedicine, Universitas Airlangga, Surabaya. Contingency Correlation analysis was performed to determinethe association between sex and behavior, Spearman’s correlation analysis was performed to determine theassociation between knowledge, education level and behavior. All data were analyzed with a significancelevel of 95%. Result: A total of respondents filled out and returned the questionnaire were 221. Eightyfive percent of respondents were females. Based on statistical analysis, there is association between sexand behavior of the implementation of EBD with 0,000 significance value, there is association betweenthe knowledge and behavior of the implementation of EBD with 0.008 significance value, and there is noassociation between the level of education and behavior of the implementation of EBD with a significancevalue of 0.458. Conclusion: There is association between sex and with behavior, but there is no associationbetween the level of education of dentistry students with evidence-based dentistry behavior.